2021
DOI: 10.1109/access.2020.3048343
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Energy Management Strategy for 24t Heavy-Duty Hybrid Emergency Rescue Vehicle With Dual-Motor Torque Increasing

Abstract: Emergency rescue vehicles are special equipment for fire, flood, earthquake and other disasters. They need to have high efficiency and high mobility under various terrain and road conditions. The fuel economy of emergency rescue vehicles is very poor in climbing and complex terrain due to the heavy weight of vehicle chassis and upper loading. The dual-motor torque increasing hybrid power system designed in this paper greatly improves the dynamic performance and mobility of emergency rescue vehicles, and the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…This approach addresses the time-consuming nature and non-guaranteed optimality of conventional FLC. Researchers, such as those in [68] and [69], have demonstrated that optimization methods can improve FLC EMS's efficiency compared to conventional approaches. The configuration of optimal FLC shares similarities with conventional FLC, differing primarily in the utilization of optimization methods to find optimal memberships and/or rule bases for the fuzzy system.…”
Section: B Optimal Flcmentioning
confidence: 99%
“…This approach addresses the time-consuming nature and non-guaranteed optimality of conventional FLC. Researchers, such as those in [68] and [69], have demonstrated that optimization methods can improve FLC EMS's efficiency compared to conventional approaches. The configuration of optimal FLC shares similarities with conventional FLC, differing primarily in the utilization of optimization methods to find optimal memberships and/or rule bases for the fuzzy system.…”
Section: B Optimal Flcmentioning
confidence: 99%
“…More specifically, an emergency rescue network is a network of rescue stations that deliver relief materials to the affected areas in an automated, intelligent, secure, and efficient manner [4] . In an emergency rescue network, the rescue stations should collaborate to make optimal material delivery decisions [5] .…”
Section: Introductionmentioning
confidence: 99%